Foucault e Deleuze: deserções, micropolíticas, resistências - Alvim, Davis Moreira (2011)
The inventory of hypotheses about the post-modernity is extensive. Generally, those who think it like a historical period and not only an aesthetic tendency indicates at least two important features: first, the victory of the ephemeral and the banality against the critical power of the modernity and, second, the new modulation or mutation of the postwar capitalism. Another direction taken by contemporary debate characterizes our times by the emergence of a new sovereign power, which makes the state of emergency a rule and turns the concentration camp into to a paradigm of government. In both cases, the resistances were subjected to silence or placed in the background. To approach the problem we propose the following question: how the resistances occur in the post-modern times? However, we must add to the problem an inflection inspired by Deleuze: how to think a resistance in itself, apart of the categories of negative? It was necessary to investigate the notion of resistance, especially in the writings of Michel Foucault and Gilles Deleuze and, in this way, determine his contributions, disagreements and meetings around the concept. We attempt to think the resistance in themselves, freeing them from exogenous factors that determine their dynamics and observing its affirmative power. We conclude that the resistances contain, by one hand, defectors and micropolitical aspects, which are primary in relation to power, and, by another hand, connectives and inventive characteristics